Study on physico-chemical features of water in Tarahara Fish Farm, Sunsari, Nepal - Thapa, Ganesh Bahadur; Pal, Joydeb (Nepalese Journal of Biosciences, 2017)
Tarahara Fish Farm includes 37 large ponds as a fish super zone. Physicochemical parameters viz., air and water temperature, pH, DO, BOD, CO2, Cl-, TA and TH of these ponds were studied for two years (Nov. 2008 to Oct. 2010). The air temperature had positive and significant correlation with water temperature (r=0.893, P<0.01) but inverse and significant correlation with DO (r = - 0.669 P<0.05) and TH (r = - 0.673, P<0.05). Both air and water temperature showed a decreasing trend during the winter months of November to January and again September to October in both years. Similarly, positive and significant correlation showed by pH with DO (r =0.660, P<0.05) and BOD (r =0.846, P<0.05); by free CO2 with DO (r=0.854, P<0.01), chloride (r=0.648, P<0.05) and TA (r=0.616, P<0.05); by DO with TA (r =0.715, P<0.01) and chloride (r =0.625, P<0.05) and by TH with TA (r= 0.592, P<0.05) but inverse and significant correlation showed by pH with water temperature (r =-0.671, P<0.05); by free CO2 with BOD (r=-0.627, P<0.05) and by DO with BOD (r = -0.810, P <0.01). The water quality parameters were within suitable range for the fish growth and breeding with small fluctuations in different months during the first and second years. Physico-chemical parameters significantly (P<0.01; 0.05) differed between different months. However, no mass mortality of fish was recorded from this site. So, the area selected as fish super zone is fruitful to meet the expected production level of fishes and fish seeds in peripheral areas.